Improving Sustainability in the Hospitality Industry - Melissen, F. W. (Frans).; Sauer, Lieke (Milton : Routledge, 2018)
Over the past few years the hospitality industry has become a lot more sustainable than it used to be. However, the industry's contribution to the sustainable development of our societies is still significantly smaller than it could be. This book specifically addresses the links between operations, tactics and strategy from a sustainable development perspective and moves beyond describing what is to reflect on what could be or even what should be, thus providing students with a concise guide for improving sustainability concepts and businesses in the hospitality industry. Each chapter uses specific cases and examples to reflect on different ways in which sustainability principles can be used for revisiting the host-guest relationship and improving the industry's business processes and models. In doing so, the book provides current and future professionals with guidelines, inspiration and a call for action to take sustainability within the hospitality industry to the next level, based on inclusiveness, equality and a sustainable relationship with our natural environment.
Your role as a hospitality professionalSustainable hospitality competencies; Summary; Food for thought; References; Index
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: hospitality and sustainability; sustainability and community; sustainable behaviour; sustainable development; sustainable hospitality operations